Huberine, a New Canthin-6-One Alkaloid from the Bark of Picrolemma huberi (2018)
ABSTRACT: A new alkaloid, Canthin-6-one, Huberine (1), together with three known compounds including 1-Hydroxy-canthin-6-one (2), Canthin-6-one (3) and stigma sterol (4), were isolated from the stem bark of Picrolemma huberi. The isolation was achieved by chromatographic techniques and the purification was performed on a C18 column using acetonitrile/water (90:10, v/v) with 0.1% formic acid as the mobile phase. The structural elucidation was performed via spectroscopic methods, notably 1D- and 2D-NMR, UV, IR, MS and HRMS. The antiplasmodial activity of the compounds was studied.